Plantas utilizadas no tratamento de malária e males associados por comunidades tradicionais de Xapuri, AC e Pauini, AM - Ferreira, Almecina Balbino [UNESP] (2015)
Malaria is a parasitic disease caused by organisms in the genus Plasmodium. Approximately 400 species of Anopheles have been described, of which 60 are implicated in the transmission of malaria in different parts of the globe. The first autochthonous case of malaria in Brazil dates to the 16th Century and arose as a natural consequence of European colonization. Beginning at the outset of Pará rubber exploration in the Amazon region, malaria became a serious public health problem, considering that many immigrants coming from Northeastern Brazil were decimated by this disease. Along the Acre and Purus rivers, ribeirinho (riverside) populations make use of numerous plant species, both native and exotic, to treat malaria and its symptoms; these populations are familiar with the plants' modes of use and habitats. The present study examined the management of wild and cultivated plants used to treat malaria and associated ailments by ribeirinho communities in the municipalities of Pauini and Xapuri in Amazonas and Acre states, respectively. During the year 2013 the present study interviewed 86 persons in nine rural communities in Pauini and Xapuri that were known for their use of medicinal plants. A total of 86 plant species were indicated by seringueiros and ribeirinhos for the treatment of malaria and for associated symptoms, while 25 species were indicated for the treatment of malaria, of which two had no previous indication of use for that purpose. Other species were indicated for the treatment of liver ailments (closely associated with malaria), headaches, body pains, inflammation of the stomach, and anemia. Collaborators described five distinct modes of preparation of the plant parts used: for 45% the leaves were used, for 30% te bark, for 10% the root, for 8% the entire plant, and for smaller percentages the bulb ...